2015
DOI: 10.1049/iet-nbt.2013.0065
|View full text |Cite
|
Sign up to set email alerts
|

Colourimetric‐based method for the diagnosis of spinal muscular atrophy using gold nanoprobes

Abstract: Although numerous molecular methods for spinal muscular atrophy (SMA) detection have been exploited, most of them are laborious, time consuming and costly. Recently, gold nanoparticles (AuNPs) have attracted attention in the field of colourimetric bioanalysis, because AuNP aggregation can be tracked with the naked eye as well as ultraviolet-visible (UV-vis) peak analysis. Here, based on a non-cross linking platform, a colourimetric-based method was used to evaluate the capability of thiolated oligo-AuNPs (Au n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…A number of researchers have performed similar experiments, and their reported results are consistent with our current findings [17,18,23,39,42,[45][46][47][48][49]. Padmavathy et al showed the dominance of the electrosteric repulsion force arising from a double-stranded target-Au-nanoprobe structure over the saltinduced aggregation process.…”
Section: Spectral Analysissupporting
confidence: 90%
“…A number of researchers have performed similar experiments, and their reported results are consistent with our current findings [17,18,23,39,42,[45][46][47][48][49]. Padmavathy et al showed the dominance of the electrosteric repulsion force arising from a double-stranded target-Au-nanoprobe structure over the saltinduced aggregation process.…”
Section: Spectral Analysissupporting
confidence: 90%
“…To fabricate the gold nanoprobe, we used the salt ageing method (Mirkin method) with a little change. [34][35][36][37] In summary, to reduce potential disulde bonds in thiol probes, we used a 0.5 M dithiothreitol solution and then desalted and puried the probes with an NAP-5 column. We determined the concentration of the probe with a nanodrop machine.…”
Section: Synthesis Of Citrate-stabilized Gold Nanoparticles and Au Namentioning
confidence: 99%
“…The change in the dispersion state of the nanoparticles results in a color change, which results in detection. 21,22 Many studies have used gold nanoparticles containing thiol-modied oligonucleotides (Au nanoprobes) for diagnosis. 23 These nanoparticles have unique optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, nanomaterials find their vital role in different biological applications [28][29][30][31][32]. The transition molybdenum metal is one of the essential micronutrients required for nitrogen fixation in many algae, including heterocyst-forming cyanobacteria [33,34].…”
Section: Introductionmentioning
confidence: 99%